Sharia-Based Investment Strategy: Optimizing Returns and Minimizing Risks in The Capital Market - Selasi, Dini; Cucu Putria, Andieni; sutono (Journal of Islamic Economic Development, 2023)
Islamic capital markets have become the focus of increasingly intense research, sparking high interest in investments that align with Islamic finance principles. This journal, entitled "Sharia-Based Investment Strategy: Optimizing Returns and Minimizing Risk in the Capital Market," comprehensively discusses key concepts in Sharia investment strategies. The importance of developing an investment strategy that combines Islamic ethical principles to achieve optimal returns. The literature study research method investigates stock selection, portfolio diversification, and risk management in the Sharia context. The discussion results highlight the diversity of existing views and strategies and challenges and opportunities in implementing Sharia investment strategies. The conclusion summarises the findings and emphasizes the urgency of developing strategies that combine Islamic finance with effectiveness and sustainability in global capital markets.